Analiza spremembe besedotvornosti pri ruskem vprašalnem zaimku čto - SoonCheon, Eom (Slavistična revija, 2013)
The purpose of the paper is to analyze the characteristics of the change and development of čto from an interrogative pronoun to a particle and the relevant mechanism of that process, and to analyze the grammatical and syntactic characteristics, discourse function, and meaning by distinguishing the stages involved in the process from the interrogative pronoun to the particle. The interrogative pronoun ultimately acquires the status of a particle after going through the stages of pronominal particle to particle pronoun by restructuralization, subjectivization, and pragmatic inference from metonymy and inference from metaphor. When the interrogative pronoun čto becomes a particle, it goes through several intermediate stages that have unique characteristics on the grammatical, syntactic, and discourse levels. The transformation of the interrogative pronoun čto into the particle čto is due to the grammaticalization phenomenon.
Keywords: gramaticalization; gramatikalizacija; interrogative pronoun; metafora; metaphor; metonimija; metonymy; Pro-form; pronoun; Russian; Russian language; ruščina; vprašalni zaimek; zaimek